Sepsis and delayed cerebral ischemia are associated and have a cumulative effect on poor functional outcome in aneurysmal subarachnoid hemorrhage - Centner, Franz-Simon; Wenz, Holger; Oster, Mariella Eliana; Dally, Franz-Joseph; Sauter-Servaes, Johannes; Pelzer, Tanja; Schoettler, Jochen J.; Hahn, Bianka; Abdulazim, Amr; Hackenberg, Katharian A. M.; Groden, Christoph; Krebs, Joerg; et al. (Frontiers in Neurology, 2024)
Objective: Although sepsis and delayed cerebral ischemia (DCI) are severe complications in patients with aneurysmal subarachnoid hemorrhage (aSAH) and share pathophysiological features, their interrelation and additive effect on functional outcome is uncertain. We investigated the association between sepsis and DCI and their cumulative effect on functional outcome in patients with aSAH using current sepsis-3 definition.Methods: Patients admitted to our hospital between 11/2014 and 11/2018 for aSAH were retrospectively analyzed. The main explanatory variable was sepsis, diagnosed using sepsis-3 criteria. Endpoints were DCI and functional outcome at hospital discharge (modified Rankin Scale (mRS) 0-3 vs. 4-6). Propensity score matching (PSM) and multivariable logistic regressions were performed.Of 238 patients with aSAH, 55 (23.1%) developed sepsis and 74 (31.1%) DCI. After PSM, aSAH patients with sepsis displayed significantly worse functional outcome (p<0.01) and longer ICU stay (p=0.046). Sepsis was independently associated with DCI (OR=2.46, p<0.01). However, after exclusion of patients who developed sepsis before (OR=1.59, 95%CI: 0.78-3.24, p=0.21) or after DCI (OR=0.85, 95%CI: 0.37-1.95, p=0.70) this statistical association did not remain. Good functional outcome gradually decreased from 56.3% (76/135) in patients with neither sepsis nor DCI, to 43.8% (21/48) in those with no sepsis but DCI, to 34.5% (10/29) with sepsis but no DCI and to 7.7% (2/26) in patients with both sepsis and DCI.Our study demonstrates a strong association between sepsis, DCI and functional outcome in patients with aSAH and suggests a complex interplay resulting in a cumulative effect towards poor functional outcome, which warrants further studies.